ROLE IN MEETING THE NEEDS OF MOTHER ON CHILD DEVELOPMENT PRESCHOOLERS - Astarani, Kili; Werdiningsih, Ayu Tabita Agustus (Jurnal Penelitian STIKES Kediri, 2012)
Development refers to changing pattern which begins in early stage of growth and continues throughout the life span. The lack of mother’s role on children basic needs fulfilment have adverse effects to children development. The purpose of this study was to analyze the correlation between mother’s role on children basic needs’ fulfilment toward preschoolers’ development aged 3-6 years old on Baptist Kediri Setia Bakti Kindergarten. The design was Analytical Correlational. The respondents were children aged 3-6 years old and their mothers, using Purposive Sampling Technique, it was obtained 65 respondents. The independent variable was mother’s role on children basic needs’ fulfilment while the dependent variable was preschoolers’ development. The preschoolers’ development consists of fine motoric development, gross motoric, language, social and personal. The data were collected using questionnaires (mother’s role) and DDST (children development). Further, those were analyzed using Spearman Rho Test with significance level α <0.05. The results showed fine motoric development p= 0.001 with coefficient correlation 0.406, gross motoric development p= 0.007 with coefficient correlation of 0.331, language development 0.369 with coefficient correlation of 0.113, social personal development p= 0.001 with coefficient correlation 0.400. In conclusion, mother’s role on children basic needs’ fulfilment had correlation showed fine motoric, gross motoric development, and social personal development toward preschoolers’ development aged 3-6 years old on Baptist Kediri Setia Bakti Kidergarten.